PENGARUH MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA DI SMP NEGERI 9 PEMATANGSIANTAR T.A 2022/2023 - Yan Verico Manik; Lois Oinike Tambunan; Yoel Octobe Purba (Universitas Islam Sumatera Utara, 2022)
This study aims to determine whether there is an effect of the Connected Mathematics Project learning model on students' connection abilities at SMP Negeri 9 Pematangsiantar T.A 2022/2023. The method used in this study is an experimental method using a Quasi Experimental Design. The sample consisted of two classes, namely the experimental class which was treated with the Connected Mathematics Project learning model and the control class which was given the conventional learning model with a total of 32 people each. Data were collected by observation, interview, test, and documentation methods. Analysis of the data requirements used is the normality test and homogeneity test. Then based on the results of hypothesis testing, it was concluded that there was an effect of the Connected Mathematics Project learning model on the mathematical connection abilities of students at SMP Negeri 9 Pematangsiantar T.A 2022/2023.